(untitled) (Bangladesh Journal of Medical Science, 2025)
The aim of the study is to develop the speed abilities of primary school children with mild myopia. Methods The pedagogical experiment was conducted for 6 months: September 2022 – February 2023. The study involved 16 primary school students who, according to the doctor’s conclusion, were diagnosed with mild myopia. A total of 72 physical education lessons were held in each group. In the control group, students studied according to the program for secondary schools under the guidance of a physical education teacher. In the experimental group, children were engaged in athletics using a specially developed method for developing the speed abilities of younger schoolchildren with mild myopia. To evaluate the results of the study, basic tests were used: catching a ruler, the frequency of hitting a tennis ball against a wall in 20 seconds, jumping rope in 45 seconds, running 30 m. Results After the end of the study in the control group, the indicators improved in the test “catching a ruler” by 1% (P>0.05), “the frequency of hitting a tennis ball against a wall in 20 seconds” by 15% (P>0.05), “jumping rope in 45 seconds” by 11% (P>0.05) and “Running 30 m” by 2% (P>0.05). In the experimental group, the indicators improved significantly in all tests: “catching a ruler” by 26% (P>0.05), “the frequency of hitting a tennis ball against a wall in 20 seconds” by 34% (P>0.05), “jumping rope in 45 seconds” by 38% (P<0.05) and “Running 30 m” by 11% (P>0.05). Comparison of indicators between students of the control and experimental groups significant changes occurred in 3 indicators (P<0.05), except for the test “The frequency of hitting the ball against the wall in 20 seconds” (P>0.05). Conclusion At the end of the pedagogical experiment, the increase in the indicators of the speed abilities of the children of the experimental group is significantly higher than that of the children of the control group. The unreliable increase in indicators in the experimental group can be explained by the short duration of the study, as well as by the fact that the program of physical education lessons included an insufficient number of exercises for the development of speed abilities. Despite this, the developed technique has a positive effect on the development of speed abilities, which means it is effective. The developed experimental technique for developing the speed abilities of primary school children with mild myopia using athletics has proven its effectiveness and can be used in physical education lessons with children with visual impairments. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 74-86